Secondary prevention of coronary heart disease: a cross-sectional analysis on the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Birck, Marina Gabriela (2019)
BACKGROUND: Coronary heart disease (CHD) remains a major cause of mortality worldwide and in Brazil. Use of standard medications after CHD has been proven to avoid new events and reduce early mortality. OBJECTIVES: This study aimed to analyze secondary prevention of CHD and its association with the base-line characteristics of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). DESIGN AND SETTING: Cross-sectional analysis on ELSA-Brasil data. METHODS: Secondary prevention of CHD recommended in standard guidelines (antiplatelet plus be-ta-blocker plus lipid-lowering drug, with or without angiotensin-converting enzyme inhibitors, ACEI, or angiotensin receptor blockers, ARB) was evaluated in relation to sociodemographic data and the time since the coronary event. The chi-square test, one-way analysis of variance (ANOVA) and Mann-Whitney test were performed, as necessary. RESULTS: Among 15,094 participants, 2.7% reported a previous diagnosis of CHD. Use of recommended drugs for secondary prevention was reported by almost 35% of the participants. Medication use for sec-ondary prevention was generally more frequent among high-income participants than among low-income participants. Use of ARB and ACEI was different between participants who had private health insurance and those who only used the public healthcare system. Men were more likely to use medication than women. The frequency with which participants used the recommended drugs was similar in all time periods after CHD, but use of only one drug increased progressively across time periods. CONCLUSION: The use of medication for secondary prevention of CHD was lower than what is recom-mended in standardized guidelines, especially among women and lower-income participants